Impact of Political Issues on Global Economic Growth: The Relationship Between Political Issues and Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Does democracy in the political arena assist or chokeeconomic development? Our conversation regarding this doubt starts with aexamine of debates in favor of and opposite democracy. Then we generalizeapproximate analyzes in which political regime is combined among determinantsof development and determine some methodological dilemmas entailed in suchanalyzes. The consideration is that social scientists know unexpectedlyminimal: our approximate is that political institutions do component fordevelopment, but approximating in terms of regimes does not seem to accumulatethe descriptive dissimilarities.